Enzymatic activity of the endoohytic Fusarium species strains isolated from wheat - Y. Bakri Bakri; M. Jawhar; M.I.E. Arabi (Advances in Horticultural Science)
Fusarium is a genus of fungi that cause some of the most important plant diseases affecting agricultural and horticultural crops. Members of the genus establish an endophytic role inside the tissue of plants and produce a wide range of biologically active metabolites and enzymes. In the present study, the enzymatic profiles of several dominant Fusarium spp. were determined under solid state fermentation and activities were detected for xylanase, lipase, amylase, polygalacturonase, filterpase, and carboxy-methyl cellulase. Each Fusarium spp. showed a wide range of enzyme activities and protein contents. The ability to produce these enzymes was distributed amongst the strains tested, however amylase and xylanase F. solani Sy7 was found in a high percentage of strains. This study provides additional information to support future research about the industrial potential of these enzyme-producing species.